Twenty-fold increase in thermonuclear reaction yield in laser driven compression - Key, M; Yamanaka, M; Cole, A; Grande, M; Rumsby, P; Lamb, M; Saadat, S; Robertson, E; Fews, A; Norreys, P; Yamanaka, C; Takabe, H; et al. (1989)
The production of large yields of thermonuclear neutrons in 12 beam laser driven implosion of deuterium filled glass microballoons of very high aspect ratio has been studied. It has been found that significantly enhanced yield is obtained when the target irradiation is symmetrical but locally concentrated. A simple model satisfactorily describes a wide range of experimental results. © 1989.